PENGARUH KANDUNGAN ASAM LEMAK BEBAS (ALB) TERHADAP PERUBAHAN DENSITAS CRUDE PALM OIL (CPO) - ALIYAH FAHMI (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2020)
Density are a physical parameter of Crude Palm Oil (CPO) quality determination which done by gravimetric method (weighing sample in a picnometer 50 mL, g/mL). Density is affected by the temperature. High temperature in CPO may cause the density become less by a little. But if we get them in lower temperature will make them in solid form and this situation is undesirable in trade industry. High temperature may cause hydrolysis reaction that add free fatty acid (FFA) content. The density changing was made with variation temperature (450C, 500C, 550C, 600C dan 650C) and FFA concentration (2%,3%,4%,5% and 6%). The result in this research was high concentration of FFA will make CPO density decreased with inreasing temperature. The linier relationship happened in same temperature (450C), the CPO density with free fatty acid content were 2%, 3%, 4%, 5% and 6% were ?= 0,8934; 0,8391; 0,8926; 0,8921 and 0,8920), so did the temperature at 500C, 550C, 600C dan 650C Keywords: Density, CPO, FFA, Temperature